Impact of preoperative thrombocytopenia on the outcome after coronary artery bypass grafting - Nammas Wail; Dalén Magnus; Rosato Stefano; Gherli Riccardo; Reichart Daniel; Gatti Giuseppe; Onorati Francesco; Faggian Giuseppe; De Feo Marisa; Bancone Ciro; Chocron Sidney; Khodabandeh Sorosh; et al. (Taylor and Francis Ltd, 2022)
The impact of thrombocytopenia on postoperative bleeding and other major adverse events after cardiac surgery is unclear. This issue was investigated in a series of patients who underwent isolated coronary artery bypass grafting (CABG) from the prospective, multicenter E-CABG registry. Preoperative thrombocytopenia was defined as preoperative platelet count <150 × 109/L and it was considered moderate-severe when preoperative platelet count was <100 × 109/L. Multilevel mixed-effects regression analysis was performed to adjust the effect of thrombocytopenia on outcomes for baseline and operative covariates as well as for interinstitutional differences in patient-blood management. Among 7189 patients included in this analysis, 599 (8.3%) had preoperative thrombocytopenia. Patient with preoperative thrombocytopenia had an increased chest drainage output at 12 h (mean, 519 vs. 456 mL, adjusted coeff. 39, 95%CI 18–60) and rates of severe-massive bleeding (Universal Definition of Perioperative Bleeding (UDPB) severity grades 3–4: 12.7% vs. 8.1%, adjusted OR 1.47, 95%CI 1.11–1.93; E-CABG bleeding severity grades 2–3: 10.4% vs. 6.1%, adjusted OR 1.78, 95%CI 1.30–2.43). Thrombocytopenia was associated with an increased risk of hospital/30-day death (3.2% vs. 1.9%, adjusted OR 2.02, 95%CI 1.20–3.42), 1-year death (5.7% vs. 3.4%, adjusted HR 1.68, 95%CI 1.16–2.44), deep sternal wound infection (3.5% vs. 2.4%, adjusted OR 1.65, 95%CI 1.02–2.66), acute kidney injury (28.1% vs. 22.2%, OR 1.45, 1.18–1.78), and prolonged stay in the intensive care unit (mean, 3.6 vs 2.8 days, adjusted coeff. 0.74, 95%CI 0.40–1.09). Similar results were observed in a subset of patients with moderate-severe thrombocytopenia (51 patients, 0.7%). In particular, these patients had a markedly higher rate of acute kidney injury (40%, adjusted OR, 1.94, 95%CI 1.05–3.57), resternotomy for bleeding (7.8%, adjusted OR 3.49, 95%CI 1.20–10.21), and severe-massive bleeding (UDPB severity grades 3–4: 23.5%, adjusted OR 3.08, 95%CI 1.52–6.22; E-CABG bleeding severity grades 2–3: 23.5%, adjusted OR 4.43, 95%CI 2.15–9.15) compared to patients with normal preoperative platelet count. Mild preoperative thrombocytopenia is associated with increased risk of severe-massive bleeding, mortality, and other major adverse events after CABG. Such risks are markedly increased in patients with moderate-severe preoperative thrombocytopenia.